Sr-Nd-Pb Isotope Evidence for Ice-Sheet Presence on Southern Greenland During the Last Interglacial - Colville, Elizabeth J.; Carlson, Anders E.; Beard, Brian L.; Hatfield, Robert G.; Stoner, Joseph S.; Reyes, Alberto V.; Ullman, David J. (Science, 2011)
To ascertain the response of the southern Greenland Ice Sheet (GIS) to a boreal summer climate warmer than at present, we explored whether southern Greenland was deglaciated during the Last Interglacial (LIG), using the Sr-Nd-Pb isotope ratios of silt-sized sediment discharged from southern Greenland. Our isotope data indicate that no single southern Greenland geologic terrane was completely deglaciated during the LIG, similar to the Holocene. Differences in sediment sources during the LIG relative to the early Holocene denote, however, greater southern GIS retreat during the LIG. These results allow the evaluation of a suite of GIS models and are consistent with a GIS contribution of 1.6 to 2.2 meters to the =4-meter LIG sea-level highstand, requiring a significant sea-level contribution from the Antarctic Ice Sheet.